2014
DOI: 10.1111/apt.12789
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing colorectal cancer and benign colorectal neoplasm in patients with chronic constipation

Abstract: SUMMARY BackgroundChronic constipation (CC) is a highly prevalent health problem, potentially associated with increased risk of colorectal cancer (CRCancer).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 33 publications
3
71
1
2
Order By: Relevance
“…In contrast to ischemic heart disease, stroke, and severe infection, constipation is not a life-threatening complication in CKD, except in rare cases of colonic bleeding due to stercoral ulcers [5]. However, several cohort studies have shown that constipation is associated with increased mortality in the general population [6], which may be explained by the relationship between constipation and colon cancer [7,8] and cardiovascular disease (CVD) [9][10][11]. Furthermore, a nationwide cohort study from the United States including 3 million veterans reported that constipation was associated with the higher incidence of CKD (hazard ratio, 1.13) and ESKD (hazard ratio, 1.09) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ischemic heart disease, stroke, and severe infection, constipation is not a life-threatening complication in CKD, except in rare cases of colonic bleeding due to stercoral ulcers [5]. However, several cohort studies have shown that constipation is associated with increased mortality in the general population [6], which may be explained by the relationship between constipation and colon cancer [7,8] and cardiovascular disease (CVD) [9][10][11]. Furthermore, a nationwide cohort study from the United States including 3 million veterans reported that constipation was associated with the higher incidence of CKD (hazard ratio, 1.13) and ESKD (hazard ratio, 1.09) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The problem is difficult to talk about because of its intimate nature, and it has been found that patients feel that staff do not pay enough attention to the problem . Further, constipation also increases the risk of comorbidities such as megacolon, intestinal impaction, volvulus, psychological conditions such as depression and mood disorders , and colorectal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The list of the excluded studies with the exclusion reasons are presented in Supplementary Material S3. Finally, ten cohort studies were included [15,[22][23][24][25][26][27][28][29][30]. The study selection process is presented in Figure 1.…”
Section: Identification and Characteristics Of The Included Studiesmentioning
confidence: 99%